Impact of Pathologists and Evaluation Methods on Performance Assessment of the Kidney Injury Biomarker, Kim-1. (July 2015) - Rouse, Rodney; Min, Min; Francke, Sabine; Mog, Steven; Zhang, Jun; Shea, Katherine; Stewart, Sharron; Colatsky, Thomas
Attempts to characterize and formally qualify biomarkers for regulatory purposes have raised questions about how histological and histopathological methods impact the evaluation of biomarker performance. A group of pathologists was asked to analyze digitized images prepared from rodent kidney injury experiments in studies designed to investigate sources of variability in histopathology evaluations. Study A maximized variability by using samples from diverse studies and providing minimal guidance, contextual information, or opportunities for pathologist interaction. Study B was designed to limit interpathologist variability by using more uniform image sets from different locations within the same kidneys and allowing pathologist selected interactions to discuss and identify the location and injury to be evaluated but without providing a lexicon or peer review. Results from this study suggest that differences between pathologists and across models of disease are the largest sources of variability in evaluations and that blind evaluations do not generally make a significant difference. Results of this study generally align with recommendations from both industry and the U.S. Food and Drug Administration and should inform future studies examining the effects of common lexicons and scoring criteria, peer review, and blind evaluations in the context of biomarker performance assessment.